Determinants of Customer Satisfaction with ATM Services: Evidence from Customers of Commercial Banks in Pokhara, Nepal - Bhattarai, Bal Ram; Gurung, Santosh Kumar; Maraseni, Manisha (Journal of Business and Management, 2024)
Background: The banking industry has witnessed the rise of various service delivery channels, including automated teller machines (ATMs). As global financial systems evolve and competition intensifies, there has been an increasing focus on examining customer satisfaction. Objectives: This study examined the determinants of customer satisfaction with ATM services among customers of commercial banks in Pokhara, Nepal. Methods: This study adopted a descriptive cross-sectional design to investigate the determinants of customer satisfaction with ATM services among commercial bank customers in Pokhara, Nepal. A self-reported survey was administered to 153 customers from various commercial banks through a structured questionnaire distributed via Google Forms. The survey comprised 29 items across six key constructs: reasonability of fees charged (5 items), frequency of problems faced (5 items), choice of ATM (5 items), usage of services (4 items), post-purchase behaviour (4 items), and customer satisfaction (6 items). Respondents rated each item on a sixpoint Likert scale, where 1 indicated strong disagreement, and 6 indicated strong agreement. Pearson correlation analysis examined the relationship between the various dimensions of ATM services and customer satisfaction. Results: The findings revealed positive correlations between customer satisfaction and factors such as post-purchase behaviour (r = 0.723, p < 0.01), reasonability of fees charged (r = 0.621, p < 0.01), choice of ATM (r = 0.605, p < 0.01), and usage of services (r = 0.478, p < 0.01). However, the frequency of problems faced (r = -0.217, p < 0.01) showed negative correlations with customer satisfaction. Conclusion: This study clearly demonstrated that customer satisfaction is strongly driven by factors such as post-purchase behaviour, the reasonability of fees charged, choice of ATM, and usage of services. However, the frequent occurrence of operational issues, such as malfunctions and service disruptions, significantly decreases customer satisfaction. These results highlight. JEL Classification: G21, M15, 031